Enhanced pyruvate dehydrogenase activity improves cardiac outcomes in a murine model of cardiac arrest - Piao, Lin (PLoS One, 2017)
RATIONALE: Post-ischemic changes in cellular metabolism alter myocardial and neurological function. Pyruvate dehydrogenase (PDH), the limiting step in mitochondrial glucose oxidation, is inhibited by increased expression of PDH kinase (PDK) during ischemia/reperfusion injury. This results in decreased utilization of glucose to generate cellular ATP. Post-cardiac arrest (CA) hypothermia improves outcomes and alters metabolism, but its influence on PDH and PDK activity following CA are unknown. We hypothesized that therapeutic hypothermia (TH) following CA is associated with the inhibition of PDK activity and increased PDH activity. We further hypothesized that an inhibitor of PDK activity, dichloroacetate (DCA), would improve PDH activity and post-CA outcomes. METHODS AND RESULTS: Anesthetized and ventilated adult female C57BL/6 wild-type mice underwent a 12-minute KCl-induced CA followed by cardiopulmonary resuscitation. Compared to normothermic (37°C) CA controls, administering TH (30°C) improved overall survival (72-hour survival rate: 62.5% vs. 28.6%, P<0.001), post-resuscitation myocardial function (ejection fraction: 50.9±3.1% vs. 27.2±2.0%, P<0.001; aorta systolic pressure: 132.7±7.3 vs. 72.3±3.0 mmHg, P<0.001), and neurological scores at 72-hour post CA (9.5±1.3 vs. 5.4±1.3, P<0.05). In both heart and brain, CA increased lactate concentrations (1.9-fold and 3.1-fold increase, respectively, P<0.01), decreased PDH enzyme activity (24% and 50% reduction, respectively, P<0.01), and increased PDK protein expressions (1.2-fold and 1.9-fold, respectively, P<0.01). In contrast, post-CA treatment with TH normalized lactate concentrations (P<0.01 and P<0.05) and PDK expressions (P<0.001 and P<0.05), while increasing PDH activity (P<0.01 and P<0.01) in both the heart and brain. Additionally, treatment with DCA (0.2 mg/g body weight) 30 min prior to CA improved both myocardial hemodynamics 2 hours post-CA (aortic systolic pressure: 123±3 vs. 96±4 mmHg, P<0.001) and 72-hour survival rates (50% vs. 19%, P<0.05) in normothermic animals. CONCLUSIONS: Enhanced PDH activity in the setting of TH or DCA administration is associated with improved post-CA resuscitation outcomes. PDH is a promising therapeutic target for improving post-CA outcomes.